PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK DENGAN MENERAPKAN MODEL PROBLEM BASED LEARNING - AGUNG MARSHAL (Jurnal Edukasi dan Penelitian Matematika, 2021)
Mathematics clearning has goals that must be achieved, one of which is it he ability to solve  mathematical problems. The poor ability of students to solve math problems is due to the sub optimal learning process. Therefore, in order to over come this problem,learning model that can improve student's mathematicall problem-solving ability is needed,one off which his a problem-based learning model. The purpose off this research his to theoretically describe whether the problem-based learning model can improve student's mathematical problem-solving ability. This type of research is literature research,which aims too improve mathematical problem-solving capabilities through problem-based learning models. The conclusion of this research is to apply problem-based learning model that has a tendency to improve student’s mathematica lproblem-solving abilities. The articles on the indicators of these abilities describe these abilities related to stages in the Problem Based Learning model.Keywords__mathematical problem solving abilities, Problem BasedILearning